Topical treatment of psoriasis - Skwira, Sylwia; Gras-Ozimek, Aleksander; Kozińska, Iga; Kozińska, Anna; Pałka, Piotr (Journal of Education, Health and Sport, 2022)
Psoriasis is an autoimmune systemic disease that affects approximately 2-3% of the population. Its symptoms, although focused mainly on the skin, can also have a negative impact on other spheres of the patient's life, including their mental state, because this illness still works with some misunderstanding on the part of society. This chronic, severe inflammatory disease affects mainly skin, but other manifestations, such as joint manifestations, may occur in about 30% of patients. One of the aims of this work is to present the topic of psoriasis, and in particular its topical treatment. It discusses the most commonly used topical preparations for the treatment of psoriasis. Currently thanks to the dynamic development in the fields of medicine, pharmacology and chemistry, schemes and specimens for the effective treatment of psoriasis have been developed. They allow to treat the main, persistent and most affecting the patient’s health symptoms, at the same time improving their quality of life. These specimens are divided into local and systemic ones. They can be used in monotherapy or in combination, depending on the severity of the disease. Topical agents have a symptomatic effect, limited to the maximum remission of skin lesions. These agents not only support the healing process, but also improve the condition of the patient’s skin, which undoubtly has a positive impact on the patient’s daily life.